Trends and Prevalence of Hospital Admissions Related to Deliberate Self-Poisoning and Used Substances in Romanian Adolescents between 2016 and 2022 - Elena Predescu; Iulia Calugar; Cristian Bibu-Monus; Roxana Sipos (MDPI AG, 2023)
Rates of self-poisoning are increasing substantially all around the world, with self-poisoning being the most common form of self-harm leading to hospitalization in children and adolescents. This study aims to investigate the trends in the number of deliberate self-poisoning admissions in Romanian adolescents during the period of 2016-2022, as well as the most frequently used substances and the impact of the COVID-19 pandemic on hospital admissions due to self-poisoning and substance use in relation to these episodes. The sample included 178 patients admitted to the Clinic of Pediatric Psychiatry in Cluj-Napoca from 2016 to 2022 due to an episode of self-poisoning. Data were collected on patients' sociodemographic characteristics, psychosocial characteristics, and medical histories. We report a slight overall increase in the self-poisoning admission rate during the studied period. There was a decrease during the initial period of the pandemic, with significantly increasing rates in the second year of the pandemic. The mean prevalence rate of hospital admissions due to self-poisoning episodes during the study period was 3.14% (95% CI 2.72, 3.63). Adolescent girls were identified as the most vulnerable group, with the female-to-male ratio increasing dramatically. In terms of substance use, benzodiazepines; over-the-counter analgesics, including paracetamol; and antidepressants were the most frequently used substances. We emphasize the importance of careful consideration in prescribing psychotropic drugs, as well as the need for regulation of over-the-counter drug dispensation.